Dynamic temperature models of a soiless greenhouse - Cunha, J. B. (2013)
In this paper climate discrete-time dynamic models for the inside air temperature of a soilless greenhouse are identified, using data acquired during two different periods of the year. These models employ data from air temperature and relative humidity.